Understanding built environment realities: Between conceptual frameworks and experimental fieldworks. (15th July 2019) - Salama, Ashraf M.
Abstract : Purpose: Following the successful transition of Archnet-IJAR to Emerald, the introduction of new process and editorial teams, and the production of the first issue last March (Volume 13, Issue 1), the purpose of this paper is to outline key aspects of the contributions published in this edition of Archnet-IJAR: International Journal of Architectural Research, Volume 13, Issue 1, July 2019. Design/methodology/approach: Premised on two generic understandings of built environment research: conceptual frameworks and experimental fieldworks, a classification of topical contents and an identification of approaches within the studies published in this edition, a narrative on evolving interests and themes is developed to outline these undertakings. Findings: Five themes are identified from 13 papers contributed by 27 researchers from academic institutions in 13 countries and territories. Themes include: complexity and prosperity of informal settlements and slums; east–west dialectics of environmental design research and sustainable urbanism; educating future built environment professionals; grassroots research and design strategies; and performance, perception and behavior. Originality/value: Understanding and appreciating various research approaches for unveiling key aspects of built environment realities including the spatial and social dimensions would facilitate effective contributions in architectural and urban research. This is coupled with the advancing thematic aspects that enthuse a re-thinking of the key purpose of architectural and urban research while stimulating future research endeavors.